Credit Where It's Due: Investigating Pathways from EITC Expansion to Maternal Mental Health - Anuj Gangopadhyaya; Fredric Blavin; Jason Gates; Breno Braga (Institute of Labor Economics (IZA), 2019)
While Earned Income Tax Credit (EITC) expansions are typically associated with improvements in maternal mental health, little is known about the mechanisms through which the program affects this outcome. The EITC could affect mental health through direct tax credit, changes in labor supply and changes in health insurance coverage of participants. To disentangle these mechanisms, we assess the effects of state and federal EITC expansion on mental health, employment and health insurance by maternal marital status. We find that federal EITC expansions are associated with 1) large positive effects on employment for unmarried mothers and 2) improved self-reported mental health for all mothers. State EITC expansion, which generate smaller changes in the effective wage rate, are associated with improvements in mental health for married mothers only and have no effect on employment for married or unmarried mothers. We find no impact of EITC expansions on health insurance coverage for married or unmarried mothers. These findings suggest that while EITC expansions improved mental health for unmarried mothers through a combination of the credit and employment, for married mothers, improved mental health is driven through the direct credit alone.
Keywords: H24; I12; I14; 330; earned income tax credit; state earned income tax credit; maternal mental health; labor supply; health insurance coverage